Cultural Heritage and Tourism: The Case of Dellys in Algeria - Necissa, Yamina; Rayane, Moussaoui (Future Science, 2024)
Cultural heritage is an invaluable resource for the development of cultural tourism. It offers a wide range of economic and social opportunities, contributing to job creation, income generation and the promotion of local identity. However, to fully exploit its potential, heritage needs to be carefully integrated into an overall tourism strategy. Such a strategy must include specific measures for the preservation and enhancement of cultural heritage. Recognizing the profound synergies between cultural heritage preservation and tourism development strategies, we undertook an in-depth analysis of the current heritage situation in the town of Dellys. This analysis identified the challenges and opportunities associated with heritage enhancement in the context of tourism and local development projects. The results reveal that the implementation of the current tourism strategy in Dellys is not fully achieving its objectives. Nevertheless, its effective realization, coupled with better coordination between players in the sector, could make a significant contribution to safeguarding, revitalizing and enhancing the town's heritage.